Design of Toba Caldera Geopark Museum in Balige With A Green Architecture Approach - Chrescensia Febriyana Sinambela; Hilma Tamiami Fachrudin (Talenta Publisher, 2022)
The Lake Toba area as a Global Geopark Network is imaged as a super destination with the world's largest and one of the deepest volcanic lakes, thus making it a world heritage with diverse diversity such as geology, biology, and culture. Lake Toba creates extraordinary natural phenomena, making this area rich in geological diversity such as expanses and rock types, and contains geological heritage values (heritage), cultural heritage, and bio-heritage that are well known International. However, attractions in the Toba Caldera Geopark area have not provided education only as a place of recreation for tourists. Therefore, it is necessary to design the Toba Caldera Geopark Museum as a place for organizing, collecting, maintaining, researching, presenting information about the benefits and potentials of the Toba Caldera Geopark area with the theme of green architecture and accommodating recreational and educational activities for visitors. This study used qualitative research methods. Several data collection, several data collection methods are used, primary data and secondary data. In designing the geopark museum utilizing the concept of energy-efficient green architecture in natural lightings such as skylights, natural ventilation, respect for the site, respect for users, and experience materials.